Loss of tubulin deglutamylase CCP1 causes infantile‐onset neurodegeneration. (12th November 2018) - Shashi, Vandana; Magiera, Maria M; Klein, Dennis; Zaki, Maha; Schoch, Kelly; Rudnik‐Schöneborn, Sabine; Norman, Andrew; Lopes Abath Neto, Osorio; Dusl, Marina; Yuan, Xidi; Bartesaghi, Luca; De Marco, Patrizia; et al.
Abstract: A set of glutamylases and deglutamylases controls levels of tubulin polyglutamylation, a prominent post‐translational modification of neuronal microtubules. Defective tubulin polyglutamylation was first linked to neurodegeneration in the Purkinje cell degeneration ( pcd ) mouse, which lacks deglutamylase CCP1, displays massive cerebellar atrophy, and accumulates abnormally glutamylated tubulin in degenerating neurons. We found biallelic rare and damaging variants in the gene encoding CCP1 in 13 individuals with infantile‐onset neurodegeneration and confirmed the absence of functional CCP1 along with dysregulated tubulin polyglutamylation. The human disease mainly affected the cerebellum, spinal motor neurons, and peripheral nerves. We also demonstrate previously unrecognized peripheral nerve and spinal motor neuron degeneration in pcd mice, which thus recapitulated key features of the human disease. Our findings link human neurodegeneration to tubulin polyglutamylation, entailing this post‐translational modification as a potential target for drug development for neurodegenerative disorders. Synopsis: Tubulin glutamylation, a neuron‐enriched posttranslational modification of microtubules, is controlled by several glutamylating and deglutamylating enzymes. A first link between tubulin glutamylation and neurodegeneration was established in mice which lacked deglutamylase CCP1 and displayed cerebellar atrophy and ataxic behavior. Biallelic CCP1 mutations were identified in patients with autosomal recessive early‐onset and often fatal neurodegeneration. Clinical presentation was variable, though global developmental delay, cerebellar atrophy and motor neuropathy emerged as key features. Disease‐associated mutations lead to absence of CCP1 or loss of enzyme activity along with dysregulated tubulin glutamylation. In addition to the long‐recognized cerebellar atrophy, CCP1‐deficient mice have motor neuron degeneration, validating these mice as a reliable animal model for the human disease. Abstract : Aberrant tubulin polyglutamylation in rare human disease is characterized by severe cerebellar atrophy and motor neuron degeneration.